Financial Crisis, Bank Behaviour and Credit Crunch - Rossi, Stefania P.S; Malavasi, Roberto (Contributions to Economics, 2016)
This book presents original contributions assessing the effects the 2008 financial crisis has had on bank behaviour, regulation and credit access. After describing some of the economic aspects behind the outbreak and later developments in the recent financial turmoil, it examines the strategic responses of banks, firms and institutions, at both the macro and micro level. In this regard, the book discusses the extent to which policies implemented by governments and monetary authorities encouraged opportunistic behaviour and produced distorted incentives and market failures. Subsequently, it presents various viewpoints on how changes in bank regulations influenced bank lending, bank risk and bank funding sources. Lastly, the book evaluates the impact of the financial crisis on the cost of funding and the shrinking credit supply, examining specific cases at the regional level in Italy.